The Philosophy of Research Methodology: A View from Islamic Civilization. - Hassan, Shaik Abdullah; Sk. Kader, Dr. Muhammad Ali (2008)

(untitled)
The aim of this article is to highlight the philosophy of research methodology as view from Islamic civilization. Scientific research has no central focus in our modern terms apart from further dominance of nature, refining our materialistic gain and maximizing the control of wealth, improving our health and live a life full of sensual pleasure with no misery. Sadly what was vision was never fully materialized, the upper echelon of the society gained the full benefit while the lower societies were left out and further denigrated.